Sensor fusion methods for high performance active vibration isolation systems. (28th April 2015) - Collette, C.; Matichard, F.
Abstract: Sensor noise often limits the performance of active vibration isolation systems. Inertial sensors used in such systems can be selected through a wide variety of instrument noise and size characteristics. However, the most sensitive instruments are often the biggest and the heaviest. Consequently, high-performance active isolators sometimes embed many tens of kilograms in instrumentation. The weight and size of instrumentation can add unwanted constraint on the design. It tends to lower the structures natural frequencies and reduces the collocation between sensors and actuators. Both effects tend to reduce feedback control performance and stability. This paper discusses sensor fusion techniques that can be used in order to increase the control bandwidth (and/or the stability). For this, the low noise inertial instrument signal dominates the fusion at low frequency to provide vibration isolation. Other types of sensors (relative motion, smaller but noisier inertial, or force sensors) are used at higher frequencies to increase stability. Several sensor fusion configurations are studied. The paper shows the improvement that can be expected for several case studies including a rigid equipment, a flexible equipment, and a flexible equipment mounted on a flexible support structure.